Characterisation of hand’s velocity in butterfly stroke according to the breathing technique - Barbosa, Tiago M. (2018)
The study of the hand s kinematics, specially his path, is one of the major points of interest for researchers in biomechanics of swimming. For exemple, Martins-Silva et al. (1999) showed the importance of all components of the hand s velocity in the intracyclic variations of the velocity of the centre of mass in butterfly.